Empirical Modelling of Nonmonotonous Behaviour of Shear Viscosity - J. David; P. Filip; A. A. Kharlamov (Advances in Materials Science and Engineering)
Almost all hitherto proposed empirical models used for characterization of shear viscosity of non-Newtonian liquids describe only its monotonous course. However, the onset of new materials is accompanied by more complicated characteristics of their behaviour including nonmonotonous course of shear viscosity. This feature is reflected not only in an existence of one extreme point (maximum or minimum), but also it can appear in both extreme points; that is, this shear viscosity initially exhibits shear thinning; after attaining a local minimum, it converts to shear thickening, and again after reaching a local maximum, it has a shear-thinning character. It is clear that, for an empirical description of this complex behaviour, a hitherto, used number of parameters (four, five) in classical monotonous models (such as Cross or Carreau-Yasuda) are no longer tenable. If more parameters are applied, there should be given an emphasis on a relatively simple algebraic form of the proposed models, unambiguity of the involved parameters, and their sound interpretation in the whole modelling. This contribution provides an overview of the existing empirical nonmonotonous models and proposes a new 10-parameter model including a demonstration of its flexibility using various experimental data.